2003
DOI: 10.1161/01.str.0000075769.09092.82
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methylenetetrahydrofolate Reductase Gene Polymorphism With Carotid Atherosclerosis Depending on Smoking Status in a Japanese General Population

Abstract: Background and Purpose-The association of the methylenetetrahydrofolate reductase gene (MTHFR) with carotid atherosclerosis remains inconsistent. This may be due to small sample size and inappropriate analysis. We investigated the association of C677T/MTHFR with blood pressure and carotid atherosclerosis in a Japanese general population. Methods-Subjects (30 to 89 years of age; 1693 women, 1554 men) who gave informed consent were randomly selected from a general population in Suita, Japan. MTHFR genotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 49 publications
4
45
0
1
Order By: Relevance
“…The MTHFR gene C677T polymorphism, which is located in the predicted catalytic domain of the MTHFR enzyme, was found to be associated with a decreased enzyme activity and an elevated plasma Hcy level (Frosst et al 1995). Individuals carrying the mutant T allele with a higher plasma Hcy level might also have a higher blood pressure (Inamoto et al 2003). Thus, the T allele of the MTHFR C677T polymorphism and the 919G allele of the MTR D919G polymorphism seem to have conflicting effects in blood pressure response to benazepril.…”
Section: Discussionmentioning
confidence: 99%
“…The MTHFR gene C677T polymorphism, which is located in the predicted catalytic domain of the MTHFR enzyme, was found to be associated with a decreased enzyme activity and an elevated plasma Hcy level (Frosst et al 1995). Individuals carrying the mutant T allele with a higher plasma Hcy level might also have a higher blood pressure (Inamoto et al 2003). Thus, the T allele of the MTHFR C677T polymorphism and the 919G allele of the MTR D919G polymorphism seem to have conflicting effects in blood pressure response to benazepril.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is strong evidence linking this polymorphism with hypertension, a number of observational studies have reported conflicting or inconclusive results. Many of the studies that failed to detect significant associations used small sample sizes or suffered possible selection bias (93,(95)(96)(97)(98)(99) . Some studies have reported a gender specific association; one large population study in >3000 Japanese individuals reported that the MTHFR 677C T polymorphism was associated with a 42 % increased risk of hypertension in women but not in men (96) .…”
Section: Novel Role Of Mthfr Genotype and Blood Pressurementioning
confidence: 99%
“…Many of the studies that failed to detect significant associations used small sample sizes or suffered possible selection bias (93,(95)(96)(97)(98)(99) . Some studies have reported a gender specific association; one large population study in >3000 Japanese individuals reported that the MTHFR 677C T polymorphism was associated with a 42 % increased risk of hypertension in women but not in men (96) . In contrast, in a Spanish cohort, the TT genotype was found to be a significant predictor of hypertension in men but not in women, however, only 26 % of the sample were females (100) .…”
Section: Novel Role Of Mthfr Genotype and Blood Pressurementioning
confidence: 99%
“…25 The C677T polymorphism of the methyleneteterahydrofolate reductase (MTHFR) gene was also found to be significantly correlated with hyperhomocysteinemia and carotid atherosclerosis in Japanese women, and the significance increased when the women smoked. 26 Thus, in individuals who are genetically sensitive to ROS, a recommendation to cease smoking and to modify lifestyle, or drug administration to reduce oxidative stress, should be given. Recent pharmacological studies have shown that the combination of pioglitazone and candesartan exerts more beneficial effects on hypertensive cardiovascular damage by increasing the suppression of ROS.…”
Section: Genetic Basis For Hypertensionmentioning
confidence: 99%